To See or Not See the Shadows. The Elusive Presence of Shadows in Reality and in your Pictures - Gómez Sánchez, Diego (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2016)
The history of the iconic representations shows that the concept of realism is neither rigid nor unchanging but, on the contrary, it is multiple and changeable, perhaps because the visual reality itself presents multiple faces to observers. Shadows are elements which, though always present in front of our eyes, are rarely taken into account when defining a picture as realistic. This article weighs the importance of the shadows as optical phenomena and aims to answer the question of why a non-shadows image can come to be believed as a faithful representation of reality.